1991
DOI: 10.1002/ppul.1950100313
|View full text |Cite
|
Sign up to set email alerts
|

Use of exercise in the management of cystic fibrosis: Short communication about a survey of cystic fibrosis referral centers

Abstract: A survey of 47 cystic fibrosis referral centers was conducted to study the use of exercise in the management of patients with cystic fibrosis (CF). A questionnaire with 5 brief questions concerning the prescription and application of exercise therapy was sent to the first 47 centers (38.5%) listed in the 1988 CF Foundation Directory, and 46 (97.9%) were returned. While all but one of the respondents recommend exercise at least to selected patients, and while 80.4% of the centers refer patients to summer camp p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 6 publications
2
8
0
Order By: Relevance
“…Similar conclusions were made from surveys investigating the use of exercise testing and training in CF centres in the different healthcare systems of the US and Germany [13,14]. Surveys in the US and Germany reported that exercise testing is performed in 43.5% and 63.0% of CF clinics, respectively.…”
Section: Discussionsupporting
confidence: 74%
“…Similar conclusions were made from surveys investigating the use of exercise testing and training in CF centres in the different healthcare systems of the US and Germany [13,14]. Surveys in the US and Germany reported that exercise testing is performed in 43.5% and 63.0% of CF clinics, respectively.…”
Section: Discussionsupporting
confidence: 74%
“…Similar figures (44 and 63%, respectively) have been reported in CF centers in the US and Germany [13,14]. Furthermore, there is a notable lack of protocol standardization.…”
supporting
confidence: 82%
“…Provision of CPET in CF Current provision of exercise testing in both clinical and research assessments remains limited [6,13,14]. As outlined by Stevens et al [6], exercise testing is underused (53% uptake) within CF clinics across the UK, despite the care teams recognizing its value [6].…”
mentioning
confidence: 98%
“…23 There has been concern about reduced oxygen saturation with exercise for some patients with CF. Henke and Orenstein found that patients with an FEV 1 Յ50% of predicted values were much more likely to have larger declines in oxygen saturation than those patients with an FEV 1 above 50% predicted.…”
Section: Discussionmentioning
confidence: 99%